SISTEM INFORMASI PENJUALAN PADA PT. MULIA SUKSES JAYA - Dimas Wijaya Saputra; Saul Paulus Liunokas; Rouli Doharma (STMIK Widuri Jakarta, 2024)
PT Mulia Sukses Jaya is a company engaged in retail, which sells kitchen utensils. Sales at the company are an important thing to support the company so that the company is progressing. Problems that occur in processing sales transaction data still use paper with sales making orders with forms even though the head office already uses a computerized system so that the relationship between sales and head office and warehouse is still manual or via email. Therefore, a web-based sales information system is needed that can facilitate the processing of sales transaction data. The system was developed using the waterfall model system development life cycle (SDLC) method, using the PHP programming language MySQL database design. The results of this study provide features in the form of orders that are directly placed in the system so that they are connected between divisions through this information system directly and provide accurate information.